The Effectiveness of Teaching Creative Writing Using Cinquain Poetry - Aryusmar Aryusmar; Winda Putria (Humaniora, 2014)
This article aims at describing the effectiveness of teaching creative writing using cinquain poetry. The research was conducted at Lia Stephanie Elementary School. The students were given a pre-test, three time meetings, and a post-test. To figure out the significant difference between students’ pre-test and post-test, research used ‘Descriptive Qualitative Analysis’ since this analysis could describe the facts found during the research and it could also explain whether the aim of this research was achieved or not. In addition, this research also observed the students during the process of learning in order to find out students’ response toward the Cinquain poetry technique. Finally, the teaching creative writing using cinquain poetry was proved to be an effective medium at Elementary School.